Perilaku Pengelolaan dan Pembuangan Sampah Pada Ibu Rumah Tangga di RW 04 Kelurahan Kedaung, Kecamatan Pamulang, Kota Tangerang Selatan - Lela Kania Rahsa Puji; Niken Ayu; Mochammad Hasan (STIKes Kharisma Persada, 2020)
Waste is a problem that must be handled and managed so that it does not cause any harmful further impacts. South Tangerang City produced 4,941 m3 / day of waste in 2015 with a service level of 59% of the total amount of urban waste. Kedaung Village located in Pamulang Subdistrict, waste management in Kedaung Village is not sufficient. Most households manage waste by burning, stockpiling it in soil (3.9%), composting it, dumping it into the river / ditch / sea and dumping it carelessly. This study was to determine the relationship of knowledge, attitudes and availability of facilities to management and disposal waste to housewife. research uses analytic research with cross sectional. Data processing by Fisher's Exact test analysis and Continuity Correction at a 95% confidence level α = 0.05. Results knowledge p-value = 0.192, attitudes p-value = 0.067 and the availability of facilities p-value = 0.191. Conclusion that there is no relationship between knowledge, attitudes, and facilities for waste management and disposal waste in Kedaung Village, Pamulang Subdistric.South Tangerang 2019.